Islamic ethical attitudes and corporate crime : evidenced from accounting profession / Sazilah Mohd Saad and Roshima Said - Mohd Saad, Sazilah; Said, Roshima (Universiti Teknologi MARA, Kedah, 2013)
The risks associated with corporate crime threaten to undermine the stability of the international financial systems. Various measures have been taken to deter these crimes at various levels with continuous commitments and efforts to reinforce good governance among public listed companies. Despite the prestigious recognitions given to Malaysian companies, the data related to corporate crime has seemed unsupportive, showing the increasing pattern of corporate crime each year. The recent years have seen the re-emergence of questioning of the ethical attitudes of those employed within the organizations. Thus, this study attempts to fill the gaps by examining the effects of Islamic Ethical Attitudes to Corporate Crimes among registered accountants in the Malaysian Institute of Accountants. In light of the Islamic governance in the Malaysians companies these days, Islamic ethical attitudes should be the best measures to be considered in deterring the escalating corporate crime incidences over the years. The findings of the study provide evidence from questionnaire that majority of the account professionals perceived to have high Islamic ethical attitudes and moderately accept a corporate crime intention. The implication of this study is to provide policy makers to instill value of Islamic ethical attitudes into code of ethics of account professionals indirectly in order to prevent corporate crime.